Evidence for Dark Matter and the Λ CDM Model - Năstase, Horaţiu [UNESP] (My University, 2019)
In this chapter we will present the evidence for Dark Matter, and the resulting “Standard Model of Cosmology,” the Λ CDM model (cosmological constant plus cold dark matter). Dark Matter is what the name suggests, matter that is dark, i.e., non-luminous. That is, matter that we cannot detect from emitted light. I will present the evidences, then review the possible candidates for dark matter, and finish describing the Λ CDM model.